2001
DOI: 10.1001/jama.286.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictive Value of Intermittent Viremia With Combination HIV Therapy

Abstract: Intermittent viremia occurred frequently and was associated with higher levels of replication (Merck 035), but was not associated with virologic failure in patients receiving initial combination therapy of indinavir-zidovudine-lamivudine (ACTG 343 and Merck 035). In this population, treatment changes may not be necessary to maintain long-term virologic suppression with low-level or intermittent viremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
250
3
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(292 citation statements)
references
References 39 publications
32
250
3
7
Order By: Relevance
“…The assay-detection threshold of 500 copies/mL was commonly used when many of our participants started HAART, but it has recently decreased to 50 copies/mL. 33,34 In summary, we found that among HIV-infected injection drug users who were on antiretroviral therapy, any alcohol use and incarceration in the 6 months prior to initiating antiretroviral therapy were negatively associated with achieving HIV-1 RNA suppression. High level of adherence in the first year of therapy, longer time on therapy, lower baseline HIV-1 RNA level, and the use of HAART were also independently associated with superior virologic outcome.…”
Section: Discussionmentioning
confidence: 69%
“…The assay-detection threshold of 500 copies/mL was commonly used when many of our participants started HAART, but it has recently decreased to 50 copies/mL. 33,34 In summary, we found that among HIV-infected injection drug users who were on antiretroviral therapy, any alcohol use and incarceration in the 6 months prior to initiating antiretroviral therapy were negatively associated with achieving HIV-1 RNA suppression. High level of adherence in the first year of therapy, longer time on therapy, lower baseline HIV-1 RNA level, and the use of HAART were also independently associated with superior virologic outcome.…”
Section: Discussionmentioning
confidence: 69%
“…Prolonged breaks in adherence may thus represent islands of infectivity where host infectiousness relates positively to pretreatment SPVL. Finally, viral “blips” (brief and intermittent periods of detectable viral load despite adherence to ART) are observed more often in hosts with high baseline SPVL (Havlir et al., 2001; Leierer et al., 2015), and infections with large or frequent blips are more likely to experience virologic failure (Easterbrook et al., 2002; Grennan et al., 2012; Laprise, De Pokomandy, Baril, Dufresne, & Trottier, 2013) and achieve higher viral rebound upon treatment interruption (Castro et al., 2013). These observations span drug types, host populations and viral clades, but collectively support the intuitive assumption that infections with high SPVL are more infectious than those with low SPVL when imperfectly treated.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have described successful modifications of the Abbot Real Time assay and the Amplicor Ultrasensitive assays, including an ultra-centrifugation step and increased sample volumes [19,21], but did not evaluate amplification of different subtypes. To our knowledge this is the first report of an ultrasensitive detection of various subtypes by a modified commercial HIV-1 RNA assay.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven patients were infected with HIV-1 subtype B. Four patients crease their sensitivity [19][20][21]. For example, Havlir, et al increased the sensitivity by using ultra-centrifugation prior to amplification with the Roche Amplicor Ultrasensitive assay [19].…”
Section: Clinical Specimensmentioning
confidence: 99%
See 1 more Smart Citation